Validation of the Informal Decoding Inventory. (March 2017) - McKenna, Michael C.; Walpole, Sharon; Jang, Bong Gee
This study investigated the reliability and validity of Part 1 of the Informal Decoding Inventory (IDI), a free diagnostic assessment used to plan Tier 2 intervention for first graders with decoding deficits. Part 1 addresses single-syllable words and consists of five subtests that progress in difficulty and that contain real word and pseudoword components. The IDI was administered to a sample of 94 first graders who attended three high-poverty schools in a rural district located in a South Atlantic state. The Test of Word Recognition Efficiency–Second Edition (TOWRE-2) was given in the same session. Internal consistency (Cronbach's α) exceeded .70 for the total scores and all but one subtest. Total scores for real words and pseudowords correlated highly with TOWRE-2 subtests. Confirmatory factor analysis substantiated the five-factor structure of the IDI, and mean comparisons affirmed the order of the subtests in all cases but one. Overall, this preliminary study affirmed the reliability and validity of the IDI. Limitations and directions for future research are discussed.